Evaluation of fibers in used in fishing lines - Mohammad Muzahir, Ahmad (2010)
This project is about the experiments conducted to prove that most of the commercial fishing lines exhibited a higher breaking strength than the actual breaking strength. Besides, this project also about the investigation of the reason why fishing line that has been used can not stand for prolonged of time. So this experiment is done by stretching a test of various types and brand names of fishing lines that have in the market nowadays and subsequently to discuss and make conclusions on issues that related to the results obtained from the study. Experiments are carried out according to Malaysian Standard that was prepared by the Technical Committee on Yarns, Threads and Twines under the authority of the Textile and Clothing Industry Standards Committee. It is based on The International Standard ISO 2062 ‘Textiles - Yarn from packages - Method for determination of breaking load and elongation at the breaking load of single strands - (CRL, CRE and CRT testers)’ with reference being made to the British Standard BS 1932 : Part 1 : 1965 ‘Methods of testing the strength of yarns form packages - Part 1 : Determination of breaking load and extension’. This project has three main objectives that must achieve that are to design a suitable of tensile test rig for fishing line and has prescribed standard test method for tensile properties of fiber that used in fishing lines, identify the mechanical properties of fishing lines and investigate the effect of environmental exposure that subjected to freshwater, seawater or salt water and natural environment expose. Based on the result of from the experiments, it is found that the specimens that were exposed to freshwater, saltwater and the natural environmental give effect to the degradation of strength of fishing line. It means that water and uv light are the factors that cause the strength of fishing lines become lower. That is the reason why fishing line that has been used can not stand for prolonged of time.